2009
DOI: 10.1111/j.1365-2702.2009.02938.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing oncology nurses’ approaches to accommodating cultural needs in palliative care

Abstract: This study demonstrated that previous experiences with people from other cultures and organisational approaches to culture and cultural care often influenced nurses' views and understandings of culture and cultural mores and their beliefs, attitudes and behaviours in providing cultural care. Relevance to clinical practice. It is imperative to appreciate how nurses' experiences with people from other cultures can be recognised and built upon or, if necessary, challenged. Furthermore, nurses' cultural competence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 18 publications
0
32
0
2
Order By: Relevance
“…Because of being at the bedside during the dying process, nurses are able to assess, identify and respond in a systematic way to patient and family fears (both existential and practical) about dying and the inevitability of death (Adams, Bailey, Anderson, & Docherty, 2011;Huang, Yates & Prior, 2009;Leung & Esplen, 2008). However, just what nurses do to identify and help manage death anxiety in older immigrants of CALD backgrounds hospitalised for EOL care is unknown.…”
Section: The "Terror Of Death"mentioning
confidence: 98%
“…Because of being at the bedside during the dying process, nurses are able to assess, identify and respond in a systematic way to patient and family fears (both existential and practical) about dying and the inevitability of death (Adams, Bailey, Anderson, & Docherty, 2011;Huang, Yates & Prior, 2009;Leung & Esplen, 2008). However, just what nurses do to identify and help manage death anxiety in older immigrants of CALD backgrounds hospitalised for EOL care is unknown.…”
Section: The "Terror Of Death"mentioning
confidence: 98%
“…Researchers involved in the efforts that cross paths with cultural practices of human subjects must be aware of the potential impact as well as the challenges these will pose to the research process. According to Huang, Yates and Prior [2], culture, which refers to practiced values, beliefs, and ways of life, influences behavioral practices of certain groups in a society.…”
Section: Introductionmentioning
confidence: 99%
“…Experienced nurses in both countries focused on their own attitudes towards patients rather than the language barrier. Huang, Yates, and Prior [10] reported that nurses' previous experiences, both personally and with patients from diverse cultural backgrounds, played an important role in shaping their approach to care. In this study, nurses utilized their previous experiences caring for patients who had different cultural backgrounds to enhance their ideas about the provision of appropriate care.…”
Section: Challenges Regarding the Provision Of Care For Culturally DImentioning
confidence: 99%
“…Furthermore, nurses' previous experiences in caring for different cultural groups enhance their ability to provide appropriate cultural care [10]. From this perspective, to improve the quality of care provided by Japanese nurses to foreign patients, it is important to understand nurses' perceptions of their previous experiences in caring for patients with diverse cultural backgrounds.…”
Section: Introductionmentioning
confidence: 99%